2014
DOI: 10.1007/s13205-014-0196-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly production of silver nanoparticles using Candida utilis and its mechanistic action against pathogenic microorganisms

Abstract: Silver nanoparticles (AgNPs) have attracted great interest due to their applications in various areas. In the present study ecofriendly biosynthesis of extracellular silver nanoparticles was carried out using Candida utilis NCIM 3469. Characterization of synthesized AgNPs was done by UV–visible spectroscopy, Scanning electron microscopy and antibacterial activity. AgNPs are found spherical in shape with size in the range of 20–80 nm. AgNPs showed antibacterial activity against pathogenic organisms such as Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 27 publications
2
52
1
Order By: Relevance
“…In another research work, Waghmare et al reported the ecofriendly extracellular biosynthesis of AgNP using Candida utilis NCIM 3469. 68 Nanoparticles were circular in shape with size inbetween 20 to 80 nm and showed antibacterial activity against pathogenic strains i.e. Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli.…”
Section: Fungi and Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…In another research work, Waghmare et al reported the ecofriendly extracellular biosynthesis of AgNP using Candida utilis NCIM 3469. 68 Nanoparticles were circular in shape with size inbetween 20 to 80 nm and showed antibacterial activity against pathogenic strains i.e. Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli.…”
Section: Fungi and Yeastmentioning
confidence: 99%
“…Table 2 shows the list of various yeasts used for the synthesis of different metal nanoparticles. [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]…”
Section: Fungi and Yeastmentioning
confidence: 99%
“…Though for centuries, natural silver has already been considered as one of the most safe and nontoxic inorganic antimicrobial agents [84]. Even silver nanoparticles have also exhibited broad-spectrum antimicrobial properties due to its unique physiochemical and biological characteristics [85]. Recently, silver NPs have shown excellent antimicrobial efficacy against certain bacterial pathogens such as Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Staphylococcus epidermis, Leuconostoc mesenteroides, Klebsiella pneumonia, and K. mobilis [84].…”
Section: Antibacterial Activity Of Mycosynthesized Nanoparticlesmentioning
confidence: 99%
“…Reason for their higher antimicrobial efficacy lies with higher surface area-to-volume ratio of AgNPs that enables Functionalized Nanomaterials them to bring large portion of Ag atoms in contact with the environment (i.e., microbial cell). However, mechanism of antibacterial activity of silver NPs has not been completely understood [84][85][86][87][88].…”
Section: Antibacterial Activity Of Mycosynthesized Nanoparticlesmentioning
confidence: 99%
“…1 Nevertheless, a few studies reported successful biosynthesis of silver nanoparticle types by single-celled fungi (i.e., yeasts), including the yeast strain MKY3, 19 Candida albicans, 20 Saccharomyces boulardii 21 and Candida utilis. 22 The use of yeasts for nanoparticles production is of particular interest for industry, because they represent the world's most industrially used microorganisms, and have been grown for decades in industrial-scale cultures for the production of key fermentation-based food and drink products such as bread, beer and wine. 23,24 While the long-term knowledge of yeast cultivation for industrial applications is a strong point in favor of the use of yeasts for nanoparticles production, published data on silver-based nanoparticles production by yeasts remains limited, and there are no studies on the characterization of yeast-derived Ag/AgCl-NPs to establish their potential for industrial application.…”
Section: Introductionmentioning
confidence: 99%